RESPON PERTUMBUHAN BIBIT KARET (Hevea brasilliensis Muell. Arg.) TERHADAP CAMPURAN PUPUK NPK DAN ARANG HAYATI (BIBIT KARET ASAL BIJI DAN APPROACH GRAFTING DENGAN JELUTUNG (Dyera lowii)) (Growth Responses of Rubber Seedlings (Hevea Brasilliensis Muell.Arg) - Anis Tatik Mariyani; . Akmal; Erik Herpada Tarigan (Bioplantae, 2012)
This research was carried out on the farmers' fields located at Jalan Lingkar Barat, Kenali Besar, Kota Baru, Jambi. With about of 35 meters altitude above sea level. The purpose is to obtain the growth of rubber seedlings, which grow from rubber seed and from approach grafting with Jelutung. The research was arranged in randomized block design (RBD) with a single factor, doses of Phonska, doses of NPK fertilizer and rice husk. The research consisted of two experiment conducted in the same time. The treatment tested in this study is P0: without Phonska NPK fertilizer and rice husk, P1: NPK fertilizer Phonska 10 g + 20 g husk polybag -1, P2: NPK fertilizer Phonska husk charcoal 20 g + 30 g polybag -1, P3: NPK fertilizer Phonska 30 g + 40 g husk/polybag. The results showed that administration of NPK fertilizer treatments and husk the rubber seedlings that is not affixed to the jelutung seedlings showed no apparent effect on the variables as height. in the number of leaf, the length of roots, and the ratio of crown roots of seedlings. Distribution of NPK fertilizer treatments and the seed husk rubber affixed with jelutung seeds showed no apparent effect on the variable of the number of leaf and length of roots nevertheless significantly affect variables as height and crown root ratio of seedlings. The conclusion of this research is the treatment dose of NPK 10 g + 20 g husk is the best dose that gives the best growth of rubber seedlings are not affixed to the jelutung seedlings. Distributon of NPK fertilizer treatment 20 g + 30 g husk is the best dose that gives the best growth of rubber seedlings seeds affixed with jelutung.Keywords: Rubber, Fertilizer NPK, biological charcoal, Approach grafting.